PELATIHAN DAN MOTIVASI SEBAGAI PREDIKTOR KINERJA KARYAWAN DEPARTEMEN PRODUKSI PT. Y BATAM - Sri Langgeng Ratnasari (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: Human Resources is an important factor for the company, because the human resources which have high performance will support the company's main goal. The company's main goal is to make the company able to survive in the middle of the higher minimum wage in Indonesia, especially in Batam. The purpose of this study was to determine the training and motivation as predictors of employee performance at Production Department PT. Y Batam partially and simultaneously. The population in this study were employees of the Production Departement PT. Y Batam, as many as 147 people, with a sample of 108 employees. Sampling techniques using simple random sampling. Data colecting is using a questionnaire. Analysis of the data is using multiple linear regression by SPSS software version 22. Results showed that training and motivation as predictors of employee performance.Keywords: Training, Motivation, Performance